ปัจจัยการสื่อสารการตลาดที่ก่อให้เกิดการใช้ธุรกิจเสริมและบริการเสริมในสถานีน้ำมันของคนกรุงเทพมหานคร - อัจฉรา พฤทธิพงศ์สิทธิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
The purpose of this research was to identify: 1) People s exposure of side business and extra business marketing information at gas stations in Bangkok. 2) The using of side business and extra business at gas stations in Bangkok. 3) Factors influencing the usage of side business and extra business at gas stations in Bangkok. 4) The correlations between integrated marketing communication factors, and the using of side business and extra business at gas stations in Bangkok. 5) The correlations between the exposure of side business and extra business marketing information and the usage of side business and extra business at gas stations in Bangkok. Self administered questionnaires for interview were used to collect data from 403 people in Bangkok Metropolis between the age of 25-60 years old. Pearson s Product Moment Correlation, Anova, t-test and Multiple Regression statistical techniques were used to analyze data through SPSS computer program. The results of this research are as follows: 1) Demographic characteristics do not correlate with the using of side business and extra business. 2) Social factors: holder s opinions for using side business and extra business do not correlate with the using of side business and extra business, however father, children and spouses are the influential persons upon side business and extra business uses. 3) For the integrated marketing communicaiton factors, it was found the correlation are as follows: (1) "Product", such as side business and extra business that serve the need of customer, speedily service and high technology have correlation with using of side business and extra business. (2) "Price", such as credit card payment and price of side business and extra business have correlation with using of side business and extra business. (3) "Place", such as branches near living area and offices area and pump jockey s neat uniform have correlation with using of side business and extra business. (4) "Promotion" has no correlation with using of side business and extra business. 4) Exposure of interpersonal and mass media do not correlate with the using of side business and extra business. Marketing media is the only factor which has the influence on using of side business and extra business, such as pump jockey wearing costume and waving. 5) There are 2 variables of integrated marketing communicaiton factors which are "sales promotion" and "price" can consequently which can be explained for the using of side business and extra business.